Behaviour change initiatives to promote a healthy diet and physical activity in European countries. Issue 1 (7th February 2013) - Weichselbaum, E.; Hooper, B.; Buttriss, J.; Theobald, C.; Sgarabottolo, V.; Combris, P.; Strigler, F.; Oberritter, H.; Cullen, M.; Valero, T.; Ruiz, E.; del Pozo, S.; et al.
Summary The health benefits of physical activity and a healthy diet are well known, yet large proportions of modern societies do not meet recommended guidelines for these behaviours. Intervention programmes aimed at changing activity and eating behaviours, ranging from individual‐level approaches to community‐wide campaigns in effects on physical activity, diet and weight loss (Norman et al. 2007). A first step in healthy behaviour promotion aimed at behaviour change is to identify the health problems of a population that are serious and/or prevalent enough to justify spending time, money and other resources (Brug et al. 2005). Many behaviour change interventions aim to tackle obesity, the prevalence of which is still rising in many European countries, which is positively associated with chronic diseases affecting the health and wellbeing of Western populations. But other common risk factors for chronic disease, such as high intakes of salt or saturated fatty acids, are also the targets of health intervention programmes in a number of European countries. This paper provides examples of intervention programmes, conducted by government and other organisations, from eight European countries that aim to change behaviour in relation to diet and physical activity. It summarises the outcomes of a workshop held during a meeting of the European Nutrition Foundations (ENF) Network in London, UK, on 25 June 2012.